P–258 Ubiquitin, in the human embryo secretome, is a biomarker for embryo viability: a potential predictor of live-births, post embryo transfer. (6th August 2021) - Venkatappa, V; Vasan, S S; Adiga, S K; Varsha, S R; Prata. Kumar, V; Sachdeva, G; Seshagiri, P B
Abstract: Study question: Whether embryo-secreted ubiquitin could serve as a predictive biomarker for embryo development and viability for assessing pregnancy outcome? Summary answer: Embryo-secreted ubiquitin concentrations showed positive correlations with (a) developing embryonic stages, (b) implantation rates, (iii) live-birth rates. Their altered levels were associated with miscarriages. What is known already: Human infertility affects 15–20% couple and is mitigated by ART approaches. Poor biological-viability of in vitro developed embryos contributes to implantation failure and low birth rates(LBR). The current morphology-based embryo selection approach has shortcomings in identifying biologically-viable embryos capable of producing live-births. Earlier studies have identified ubiquitin as a biomarker for embryo developmental competence. However, there have been no studies on estimations of ubiquitin in embryo-spent medium samples (E-SMs) and their correlative analysis with embryo-quality score and pregnancy outcome. Hence, such studies are required to establish whether or not ubiquitin could be a biomarker predicting pregnancy outcome. Study design, size, duration: This was a retrospective, multi-centric study performed between July 2018 and September 2020. A total of 574 E-SMs (from 574 individual embryos), from 325 infertile women, were analysed for ubiquitin levels. Frozen E-SMs post-thaw were subjected to sandwich ELISA (Mybiosource, USA). Correlation analysis was performed on ubiquitin levels with developing embryonic stages and their scores, implantation rates (IRs) and pregnancy outcomes in terms of LBR. Participants/materials, setting, methods: We measured ubiquitin levels in E-SMs obtained from three embryonic stages i.e., cleavage-stage (2–10-cells; n = 182), morulae (n = 102) and blastocysts (n = 290). Ubiquitin concentrations among three developmental stages were compared and analysed using the Student's t-test/ANOVA (P ≤ 0.05), followed by Tukey posthoc test. Levels of ubiquitin were correlated (using Pearson/Spearman analysis) with (a) developing embryonic stages, (b) embryo morphology, (c) IRs, and (d) pregnancy outcomes in terms of LBR. Main results and the role of chance: Of 574 E-SMs analysed, 540 (94.07%) had detectable ubiquitin levels (pg/ml) and they varied in an increasing manner across developing embryonic stages and, across the three clinics. We observed a significantly different (p < 0.0001) levels of ubiquitin in three sets of secretors i.e low (153.1 ± 5.4; n = 219), medium (498.9 ± 15.7) & high (1615 ± 46.5) secretors. Levels of ubiquitin among three developmental stages were significantly (p < 0.05) different under FET, but not with fresh-ET categories. Ubiquitin levels were independent of cleavage-stage morphology score but showed a positive correlation with blastocyst grades. Also, we observed a significant (p < 0.05) positive correlation of ubiquitin levels with implantation rates. Importantly, ubiquitin levels were higher in E-SMs of embryos which gave live-births vis-à-vis those with no-births. Moreover, altered levels (very high low) were associated with those embryos which resulted in miscarriages. This is the first report which measured ubiquitin in individual hE-SMs from three developing embryos and showed a development stage-wise positive correlations as well as a significant association (p < 0.0001) of ubiquitin levels with implantation and live-birth rates. Limitations, reasons for caution: Observed variations in levels of ubiquitin across clinics could be attributed to (i) oocyte/sperm donors' variation and their infertility status (i) IVF-ET protocol differences. A large multi-centric cohort studies are required to establish the predictive value of ubiquitin for assessing embryo-viability and pregnancy outcome in term of live-births. Wider implications of the findings: For the first time, our multi-centric study showed developmental stage-specific changes in ubiquitin levels. It could be a valuable biomarker of embryo-viability and to predict IR and live-births. Ubiquitin, as a biomarker, could be a valuable adjunct to currently practicing embryo score system for selecting transferable quality embryos. Trial registration number: Not applicable